(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Physical Education, Sports, and Health (PJOK) learning requires innovative instructional approaches that encourage active student participation and improve learning outcomes. However, the mastery of underhand volleyball serving among students often remains unsatisfactory due to teacher-centered learning, limited feedback, and low student engagement during practice activities. This study aimed to describe the implementation of the reciprocal teaching method and examine its effectiveness in improving underhand volleyball serve learning outcomes among Grade XI-2 students at State Senior High School 2 Martapura. This research employed a Classroom Action Research (CAR) design conducted in two cycles involving 35 students as research subjects. Data were collected through underhand serve skill tests and classroom observation sheets. The obtained data were analyzed using descriptive quantitative techniques to determine improvements in learning achievement and classical learning completeness. The findings revealed a consistent improvement in students’ underhand serving performance throughout the intervention. Classical learning completeness increased from 42.86% in the pre-cycle stage to 62.86% in Cycle I and further improved to 88.57% in Cycle II, exceeding the predetermined success criterion of ≥80%. In addition, the average class score increased substantially from 59.74 in the pre-cycle to 78.09 at the end of Cycle II. Observation results also indicated greater student participation, collaboration, responsibility, and engagement during learning activities. In conclusion, the reciprocal teaching method effectively improves underhand volleyball serve learning outcomes and promotes active student involvement in PJOK learning. The role-switching mechanism between doer and observer, supported by structured criteria sheets, provides meaningful feedback that enhances both technical skill mastery and collaborative learning experiences.